1957
DOI: 10.1139/m57-102
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Mode of Division of the Nuclei in the Yeast Cells and Mycelium of Blastomyces Dermatitidis

Abstract: The nuclei in the yeast cells and mycelium of Blaston~yces dermatitidis were studicd in the living statc and in hxed preparations stained by various techniques. Yeast cells and mycelium are ~nultinucleate. Interdivisional and recently divided nuclei migrate into the yeast buds. Nuclear migration also occurs from one cell to another via the pores in the septa of elongated yeast cells and mycelium. Interdivisional nuclei in yeast cells and mycelium are composed of a spherical Feulgen-negative central body envelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
0

Year Published

1958
1958
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 0 publications
6
12
0
Order By: Relevance
“…Figs. 6,8,10,12,13). Nuclear migration in the hyphae of T. mentagrophytes was similar to that reported earlier by Dowding and Bakerspigel (25) and later by the writer in the report by Robinow and Bakerspigel (39).…”
Section: Generalsupporting
confidence: 86%
See 2 more Smart Citations
“…Figs. 6,8,10,12,13). Nuclear migration in the hyphae of T. mentagrophytes was similar to that reported earlier by Dowding and Bakerspigel (25) and later by the writer in the report by Robinow and Bakerspigel (39).…”
Section: Generalsupporting
confidence: 86%
“…However, nuclei in neighboring cells may either be in a different stage of division or, more commonly, interdivisional. It should be emphasized here that similar relationships were observed previously in the somatic hiphae of other imperfect fungi and in the basidiomycete, Sclzizoplzyllurn commune (6,10,12,13). In contrast, nuclei in somatic hyphae of phycomycetes, such as Endogone sphagnophila and species of Saprolegnia, as well as in the ascomycetes Gelasinospora tetrasperma and Neurospora crassa, do not divide simultaneously within the boundaries of a cell (7,8,9,11).…”
Section: Generalsupporting
confidence: 82%
See 1 more Smart Citation
“…For these reasons comparison of the staining procedure used here with that of other i~ivestigators may not explain their failure to clemonstrate mitotic figures. However, optimum staining with Giemsa's stain was achieved in 25 ~n i i i~~t e s in the present i~ivestigation, and the use of much longer periods described by other investigators (1,14) was found to give overstained preparations in which neither indiviclual chromosomes nor stages of division coulcl be distinguished.…”
Section: Discussionmentioning
confidence: 49%
“…For example, condensed chromatin has a structural role in supporting nuclear movement and/or changes in the morphology of the nucleus (Gerlitz et al, 2013) which are required for important processes such as an efficient cell migration (Gerlitz and Bustin, 2010) and fungal mitosis, in which chromosomes must condense to migrate through the extension into the daughter (Straube et al, 2005). Furthermore, during nuclear division in yeast, the chro- matin condenses, then elongates, and finally pulls apart to form two sister nuclei (Bakerspigel, 1957).…”
Section: Could Sugar Cane Glycoproteins Inhibit Germination By Means mentioning
confidence: 99%